Psychosocial intervention in mental health for teachers: a narrative review - Trindade, Magliane Soares (2022)
Knowledge in mental health for teachers is essential to identify risk and protection factors, mental vulnerabilities, the development of help and support skills, the demystification of stigmas and, above all, the approach to health services for referral and treatment. precocious. However, there are few studies that compile findings from psychosocial interventions in mental health for teachers. The present study seeks to fill this gap through a narrative literature review with the objective of analyzing the characteristics of interventions carried out in different countries to increase knowledge and sensitize the community. The interventions selected in the national and international literature have teachers as their target audience and use both virtual and face-to-face approaches in the knowledge construction process. The studies point to positive results for the promotion of mental and emotional health, the improvement of teachers' knowledge and the reduction of stigma. When considering the strategic position of observation educators and daily contact with students, this study can contribute to continuing education and updating about psychosocial interventions in a short period of time.